COOPERATION BETWEEN INDONESIA AND BRITAIN IN DEALING WITH THE THREAT OF CYBET CRIME IN 2018 - Andre Helvani Ginting; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The focus of this research is on cybersecurity cooperation between Indonesia and the UK in 2018. Indonesia and the UK, which are geographically quite far apart but both face the threat of borderless cybercrime, decided to cooperate in cybersecurity. The UK, which is one of the top countries in the cybersecurity index, is willing to work with Indonesia to realize its interests in the post-Brexit Asia Pacific region. Indonesia, which is ranked in the middle of the cybersecurity quality index, views this cooperation as a stepping stone that can improve the quality of its cybersecurity. The purpose of this study is to provide an analysis of the implementation of the cooperation agreed by the two countriesThe author collects data from various journals, official documents, theses, books and articles on the internet to analyze the implementation of cybersecurity cooperation between Indonesia and the UK. The research technique used is document study. This study uses the level of systems analysis and the theory of Dillemas of Common Aversion proposed by SteinThe realization of the cooperation, although not all have been implemented, has been carried out in accordance with three of the five points of the agreed contents of the MoU, namely the Implementation and Development of the National Cyber Security Strategy, Cyber Security Training and Campaign, and Capacity Building. Two points that have not been implemented are Cyber Crime and Cyber Incident Management. It is hoped that this cooperation can be carried out in accordance with the initial agreement, and it is hoped that this cooperation can be a reflection and the right moment for both countries to achieve their respective national interests.Keywords : cyber security, cyber crime, cyber attacks